Comparison of histomorphometric and radiographic effects of growth guidance with tension-band devices (eight-Plate and FlexTack) in a pig model. (4th May 2021) - Sattelberger, Julia; Hillebrand, Hauke; Gosheger, Georg; Laufer, Andrea; Frommer, Adrien; Appelbaum, Sebastian; Abood, Ahmed Abdul-Hussein; Gottliebsen, Martin; Rahbek, Ole; Moller-Madsen, Bjarne; Roedl, Robert; Vogt, Bjoern
Abstract : Background and purpose — Temporary hemiepiphysiodesis for growth modulation in skeletally immature patients is a long-known technique. Recently the use of tension-band devices has become popular. This study compares 2 tension-band implants (eight-Plate and FlexTack) regarding their effects on the growth plate. Animals and methods — 12 pigs in 2 equally sized groups (A and B) were investigated. The right proximal medial tibia was treated with either eight-Plate or FlexTack. The left tibia of the same pig was treated with the opposite implant. After 9 weeks all implants were removed. Animals in group B were then hosted for another 5 weeks. Histomorphometric analysis of the growth plate was carried out after 9 and 14 weeks, respectively. Radiographs were taken at implantation, removal, and after 14 weeks. Results — Both tension-band devices achieved a statistically significant and clinically relevant growth inhibition, whereas the effect appeared to be more distinct after the use of FlexTack. Implant-related complications or physeal damage was not observed. After implant removal, rebound phenomenon was radiologically observed in all cases. The growth plates treated with eight-Plate showed a paradox reversal of the zonal distributions, with an increase of the proliferative zones at the previously arrested medial aspect of the physis and a decrease laterally. Interpretation — Both eight-Plate and FlexTack proved to be appropriate devices for growth-guiding treatment. The radiographic evaluation showed a change in angular axes after treatment with each implant, while the correction appeared to be faster with FlexTack. The paradox cartilaginous reaction observed after removal of the eight-Plate might be a histopathological correlate for rebound phenomenon.